Evaluasi Kualitas Layanan E-Government menggunakan Metode E-Govqual dan Importance-Performance Analysis (IPA) (Studi pada Sistem Informasi Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Bogor) - Seno Naufal Muhammad; Hanifah Muslimah Az-Zahra; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on data obtained from observations at the The Investment and Integrated One-Stop Services Office in Bogor District (DPMPTSP). This study aims to determine the priority attributes and produce recommendations that can be given to improve the quality of e-Government services at DPMPTSP Bogor Regency. To assess the quality of website services 6 dimensions and 24 e-Govqual attributes are used. Of the 100 respondents used as research samples, the results of the IPA analysis at the suitability level have an average value of 94.82% and the value of the gap level has a GAP value of â‰¤ 0 which is -0.20, meaning that the performance of website services has not been able to meet user expectations. Furthermore, from the results of the quadrant analysis, obtained 5 attributes with top priority and 7 attributes with low priority for service improvement. Recommendations are given based on literature or theory for attributes that need to be improved in order to improve the quality of website services.